Optoelectronic Transimpedance Converter Based on MOS Photovaricap for High Resistive Gas Sensors - Semerjyan, B. O.; Kananov, D. A.; Alexanyan, M. S.
The gas detectors consist of two parts: metal-oxides gas sensor and transducer. The sensing material is made of a thin semiconductor layer. The transducer is responsible for converting the change in the several physical parameters of the thin sensitive layer into a measurable signal. Due to the high output resistance of high resistive gas sensors and the low input currents of amplifiers, electrometric cascades are employed, followed by the conversion of the gas sensors small direct current into an active current signal using a mechanical modulator (dynamic capacitor) to enhance sensitivity and stability. The aim of this research is to analyze the main characteristics of a novel type of dynamic capacitor that utilizes a surface metal-oxide-semiconductor (MOS) photovaricap (PV) as the regulating element when detecting signals from high resistive gas sensors. For the creation of surface MOS PVs, samples of p-Si with varying resistivity were chosen. A thin layer of SiO2 was deposited on these samples, onto which a translucent metallic electrode was applied. Modulation of the PV capacitance was achieved by illuminating it with a gallium arsenide LED. As a result, the capacitance of the PV is changed, producing a variable voltage across the load resistor, which was then amplified and recorded. It was observed that the settling time of the useful signal is determined by two factors. The first is the RC chain composed of the load resistance of the gas sensor and the input capacitance of the PV, and the second is slow relaxation phenomena in the structure of the MOS PV that lead to the screening of the induced charge. Characteristics of the MOS PV as a dynamic capacitor and the features of the photo capacitance as a semiconductor element, in turn, determine the transimpedance conversion coefficient. The conducted research showed that MOS PVs can be applied to register small DC currents and voltages from high resistive gas sensors. In this case, ordinary narrowband or wideband amplifiers with relatively low input resistance can be used instead of electrometric amplifiers with mechanical dynamic capacitors. The considered circuit has been experimentally tested with commercial resistors.
Keywords: Physics